Environmental change and foreign policy [ theory and practice - Harris, Paul G. (Routledge advances in international relations and global politics, 2009)
Introduces the concepts and theories of environmental foreign policy and explores how countries have approached different issues to examine the role of foreign policy politics in protecting the environment.